Could Renewable Energy Use Boost Goods Export Performance in ASEAN? - Khairunnisa, Sherina Rafidah; Oktora, Siskarossa Ika (UI Scholars Hub, 2024)
ASEAN economic integration increases trade opportunities and also triggers an increase in carbon emissions, especially from exports of goods. ASEAN needs to switch to renewable energy to improve the performance of goods exports. This study analyzes the influence of renewable energy on goods exports in ASEAN, 2010–2020. The results show that renewable energy positively impacts the performance of goods exports. Based on the results of this research, it is hoped that the government in each ASEAN country can strengthen regulations and policies on the use of renewable energy by providing incentives for producers and exporters who use renewable energy.